The Use Of Inquiry Learning Strategies As An Effort To Develop Children’s Creativity - Salpina .; Dwi Adhinda Junaidi Putri; Nurhikmah Pohan; Luluk Mukaromah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
Strategy is essential in developing all aspects of early childhood development, including in developing aspects of children's creativity. However, some educators sometimes forget the role of strategy in the process of developing children's creativity. Therefore, this study analyzed the use of appropriate strategies to develop children's creativity. This study used an inquiry learning strategy to analyze the process of using inquiry learning strategies in optimizing children's creativity. This study used a qualitative research method with group B children in TK Jeumpa Ban Kemang as the research subjects. This study also used interview data collection techniques, observation, and documentation with analytical techniques, Miles and Huberman. Based on this, the results obtained that the inquiry strategy was very appropriate to be used as a way to increase children's creativity.